Phosphorescent Platinum(II) Complexes with C^C* Cyclometalated NHC Dibenzofuranyl Ligands: Impact of Different Binding Modes on the Decay Time of the Excited State. Issue 37 (27th July 2015) - Tronnier, Alexander; Wagenblast, Gerhard; Münster, Ingo; Strassner, Thomas
Abstract Two C^C* cyclometalated platinum(II) N‐heterocyclic carbene (NHC) complexes with the general formula [(C^C*)Pt(O^O)] (C^C*=1‐dibenzofuranyl‐3‐methylbenzimidazolylidene; O^O=dimesitoylmethane) have been synthesized and extensively characterized, including solid‐state structure determination, 195Pt NMR spectroscopy, and 2D NMR (COSY, HSQC, HMBC, NOESY) spectroscopy to elucidate the impact of their structural differences. The two regioisomers differ in the way the dibenzofuranyl (DBF) moiety of the NHC ligand is bound to the metal center, which induces significant changes in their physicochemical properties, especially on the decay time of the excited state. Quantum yields of over 80 % and blue emission colors were measured.